IMPLEMENTING AUGMENTED REALITY TO PROMOTE ENGLISH ORAL PRODUCTION, INTERACTION, AND ENGAGEMENT OF THAI EFL: A CASE OF TERTIARY THAI DANCE CLASSROOM - Itsariphak Hongnimitchai; Nattharmma Namfah; Punwalai Kewara, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The development of technology makes AR learning activities in the classroom more significant. Due to the Covid 19 pandemic, AR learning activities are considered to adapt in the online classroom. This paper aims to validate the idea of learning activities to enhance speaking production by using augmented reality techniques in teaching the English language at the university level in Thailand. The English learning lesson plan with an AR application was designed and employed in the English classroom to examine students' performance using an AR application in English classes. Fifty students were selected to participate by purposive sampling. The data were obtained from observation, pre-test/post-test, and questionnaires. The finding of this study showed that the Augmented Reality learning activities combined with the Task-based learning approach encourage students to participate in activities and improve student motivation in language learning. Thus, a higher motivation increases language achievement.